PENGARUH PENGGUNAAN MODEL INKUIRI TERHADAP HASIL BELAJAR ILMU PENGETAHUAN ALAM DI SEKOLAH DASAR - Haniah, Asri Arifatul; Rosnita, Rosnita; Sugiyono, Sugiyono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The purpose of this research was to know the impact of Inquiry Model on the learning outcomes of natural science student class v in Elementary School 30 south Pontianak. The experimental research method was used in this research. The form of the experimental research used was pre-experimental design which in one group pretest-posttest. Population in this research is all students grade V which consisted of 110 people. Sample in this research were students grade 5 which consisted of 30 people. Instrument gatherer data of student learning the test results obtained from pre test and post test. The results of dats analysis showed that mean score of the student?s post-test was 69,6. Based on the t-test analisis, thitung of (8,84) and ttabel (1,697). Which means, thitung (8,84) > ttabel (1,697), thus then Ha accepted. The result of effect size was 1,80 which mean high criteria on ES>0,8. This means that learning with the use of kind of Inquiry models difference that high evolution learning outcomes from the classroom v in Elementary School 30 south Pontianak. Keyword : Inquiri Model, Study Result, Natural Science